ASME 2015 Nuclear Forum 2015
DOI: 10.1115/nuclrf2015-49185
|View full text |Cite
|
Sign up to set email alerts
|

A Supercritical CO2 Brayton Cycle Power Converter for a Sodium-Cooled Fast Reactor Small Modular Reactor

Abstract: Although a number of power conversion applications have been identified or have even been developed (e.g., waste heat recovery) for supercritical carbon dioxide (S-CO2) cycles including fossil fuel combustors, concentrated solar power (i.e., solar power towers), and marine propulsion, the benefits of S-CO2 Brayton cycle power conversion are especially prominent for applications to nuclear power reactors. In particular, the S-CO2 Brayton cycle is well matched to the Sodium-Cooled Fast Reactor (SFR) nuclear powe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 0 publications
0
17
1
Order By: Relevance
“…It is based on the selection of two dimensionless numbers, specific speed (ns) and specific diameter (ds), in conjunction with the use of Balje's ns-ds diagrams [57]. ns and ds can be determined from equation (31) and equation 32:…”
Section: Turbomachinery Design and Sizing Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…It is based on the selection of two dimensionless numbers, specific speed (ns) and specific diameter (ds), in conjunction with the use of Balje's ns-ds diagrams [57]. ns and ds can be determined from equation (31) and equation 32:…”
Section: Turbomachinery Design and Sizing Methodologymentioning
confidence: 99%
“…Recent times has witnessed a renewed interest in s-CO2 cycle [16] as PCS for nuclear power [17][18][19] and other heat sources such as concentrated solar power [20][21][22], fuel cell [23], coal [24] and waste heat [25]. In literature, s-CO2 cycle has been investigated as alternative to steam cycle for SFR application [3,[26][27][28][29][30][31][32]. All the studies agreed on the benefits of s-CO2 CBC power conversion system for SFR including higher efficiency (about 44%) and smaller footprint.…”
Section: Introductionmentioning
confidence: 99%
“…The researchers demonstrated that SCO 2 power conversion system allows an achievement of well plant efficiencies at moderate core outlet temperatures and makes it easier to eliminate contamination if fission product leakage. 1 Sienicki et al 18 concentrated on the SCO 2 Brayton cycle power conversion for a sodium-cooled fast reactor (SFR) and stated that recompression closed Brayton cycle can offer a reasonable temperature and significant benefits to the SFR. Moreover, they demonstrated that the SCO 2 Brayton cycle power converter can eliminate sodium-water reactions as well as can reduce the space requirements and cost.…”
Section: Applicability Of Sco 2 Cycles To Generation IV Reactorsmentioning
confidence: 99%
“…Analysis was performed for S-CO 2 cycles developed for advanced fast reactor (AFR-100) and advanced burner reactor (ABR-1000) reactor applications [3], [4]. Detailed calculations for the AFR-100 plant will be presented and the ABR-1000 plant is used for comparison between different cooling options.…”
Section: Department Ofmentioning
confidence: 99%
“…shows the effect of water flow rate and temperature on the cooling tower parameters for lowest power consumption option assuming that power plant is setup in Idaho Falls. For constant ambient air and water conditions, the optimum calculated from Equations(4) and(5)is constant irrespective of the water flow rate. Hence, as the water flow rate decreases the required volumetric flow rate of air decreases leading to a total reduction of floor area (A floor ) as can be seen inFig.…”
mentioning
confidence: 99%